Technologies for implementation and management of development projects - Abilkair Armanuly; Andrey Frolov; Shalbayeva Sholpan Eslambekovna (European Research Materials, 2023)
This scientific article is devoted to the technologies for implementing and managing development projects in the discipline of management, in particular, the Scrum, Agile and Kanban methodologies. The authors of the article substantiate the relevance and novelty of the introduction of modern project management technologies and explain how the Scrum, Agile and Kanban methodologies can improve the efficiency of projects and reduce their execution time, as well as stimulate the development of the company in which they are being introduced. The article discusses the basic principles of each methodology and describes examples of their application in practice. The authors also analyze the results of the introduction of these technologies and confirm the hypothesis that they allow achieving better results in the management of development projects.